PENGARUH KUALITAS PRODUK, DESAIN DAN HARGA PRODUK TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PRABOTMAMA DI SHOPEE) - Rizka Nur Yuliati; Budi Istiyanto (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
The background to this research is the development of marketplaces in the digital era where purchases of various kinds of products can be accessed anytime and anywhere, this creates opportunities for people to create the business ventures they desire. The aim of this research is to find out whether product quality, product design and product price influence Prabotmama consumer purchasing decisions at Shopee. The sample was 96 respondents calculated using the Rao Purba (1996) formula. “This analysis technique uses multiple linear regression analysis, t test, and analysis of the coefficient of determination using SPSS version 25. Based on the results of the t test, it shows that product quality (X1) and product design have no significant effect on purchasing decisions, while the price variable (X3) has an effect. significant to purchasing decisions.”